On the production of He, C, and N by low- and intermediate-mass stars: A comparison of observed and model-predicted planetary nebula abundances - Henry, R. B. C. (2018)
The primary goal of this paper is to make a direct comparison between the measured and model-predicted abundances of He, C, and N in a sample of 35 well-observed Galactic planetary nebulae (PNe). All observations, data reductions, and abundance determinations were performed in house to ensure maximum homogeneity. Progenitor star masses (M ≤ 4M⊙) were inferred using two published sets of post-asymptotic giant branch model tracks and L and Teff values. We conclude the following: (1) the mean values of N/O across the progenitor mass range exceeds the solar value, indicating significant N enrichment in the majority of our objects; (2) the onset of hot bottom burning appears to begin around 2 M⊙, i.e. lower than ~5M⊙ implied by theory; (3) most of our objects show a clear He enrichment, as expected from dredge-up episodes; (4) the average sample C/O value is 1.23, consistent with the effects of third dredge up; and (5) model grids used to compare to observations successfully span the distribution over metallicity space of all C/O and many He/H data points but mostly fail to do so in the case of N/O. The evident enrichment of N in PN and the general discrepancy between the observed and model-predicted N/O abundance ratios signal the need for extra mixing as an effect of rotation and/or thermohaline mixing in the models. The unexpectedly high N enrichment that is implied here for low-mass stars, if confirmed, will likely impact our conclusions about the source of N in the Universe.